Desain Aplikasi Sistem Informasi Akuntansi untuk Usaha Bengkel Studi Kasus pada AA Cempaka Auto Service - Surya, Firman; Santi, Elfitri; Yentifa, Armel; Frima, Rini; Djefris, Dedy (Akuntansi dan Manajemen, 2020)
This study aims to design an accounting information system application in AA Cempaka Auto Service workshop. Case study used as research approach. The application design process begins with studying the forms and reports that are required by the workshop business i.e purchasing form, sales form, general journal form, vehicle service record, debt payment and receivables. Required reports consist of transaction journal records, general ledger, balance sheet, income statement, balance sheet, inventory position, and vehicle service record. Application development stage using Microsoft Access 2007 software and VBA facilities for automation of journal posting and inventory cost calculation based on moving average method. The next step is to test the application to get sufficient confidence in transaction processing by comparing the results of the processing with the manual calculations performed. The implementation process is carried out by converting the initial data on the conversion date and inputting the transaction up to the company's operating date. After carrying out the implementation and conversion, the final stage is to carry out training to users and carry out the process of improvement and adjustments to the application based on feedback received from the user. The system design and implementation process have been deemed successful after the user has stated that the application has met all user needs and is operating properly.